Research on basin effect based on 2-D geophysical prospecting profile - Wang, Chong; Qi, Wenhao; Bo, Jingshan; Wang, Fuyun; Wang, Shuaijun; Xin, Hailiang (Frontiers in Earth Science, 2023)
The basin effects alter the frequency content, amplitude and duration of seismic waves with different depth and shape basin. In this paper, we selected 2-D geophysical profiles spanning the Weihe Basin with large area and the Luoquanli Basin with small area. Based on the velocity structure data of the two geophysical profiles, 2-D finite element models were established to analyze the influences of the sedimentary layer in a broad basin and the basement geometry of a small basin on the basin effects using the spectral element method. The results showed that the sedimentary deposits in the basin could significantly amplify the ground motion, and the diffraction waves generated by the lateral inhomogeneity of the basin could prolong the duration of the ground motion. The highlight of this paper, our results showed that the amplification characteristics were controlled by the velocity mean in the vertical direction of sedimentary deposits (vp < 4.5 km/s) for a broad basin with small depth-to-width ratio as Weihe Basin, while the amplification characteristics were dominated by basement geometry of the small basin with large depth-to-width ratio as Luoquanli Basin. In this study, a high-resolution 2-D geophysical refraction profile was directly used to construct a finite element model to study the basin effects, which provided a new method of studying the basin effects.